Mechanical Alloying of Metal–Organic Frameworks. Issue 9 (23rd January 2017) - Panda, Tamas; Horike, Satoshi; Hagi, Keisuke; Ogiwara, Naoki; Kadota, Kentaro; Itakura, Tomoya; Tsujimoto, Masahiko; Kitagawa, Susumu
Abstract: The solvent‐free mechanical milling process for two distinct metal–organic framework (MOF) crystals induced the formation of a solid solution, which is not feasible by conventional solution‐based syntheses. X‐ray and STEM‐EDX studies revealed that performing mechanical milling under an Ar atmosphere promotes the high diffusivity of each metal ion in an amorphous solid matrix; the amorphous state turns into the porous crystalline structure by vapor exposure treatment to form a new phase of a MOF solid solution. Abstract : High and dry : Solvent‐free mechanical milling promotes the high diffusivity of metal ions for two distinct metal–organic framework (MOF) crystals in the solid state. Furthermore, the process induced the formation of a new phase of a MOF solid solution.